Clinical response to Rifaximin amongst irritable bowel syndrome (IBS) patients at tertiary level hospital in Nepal - Karki, Binod; Sherpa, Tshering Wangdi; Deo, Rajeeb Kumar; Thapa, Pukar (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Irritable Bowel Syndrome (IBS) is common in patients with abdominal symptoms resulting in significant healthcare expenses. The diagnosis relies on ROME criteria, emphasizing recurrent abdominal pain over three months with changes in defecation patterns and stool appearance. Various treatment options are available for IBS including the role of antibiotics such as Rifaximin. The study aimed to assess the efficacy of rifaximin in Nepalese IBS patients.Method: This was a prospective observational study done in a Nepalese tertiary referral hospital for a period of one year after obtaining the ethical approval. All diagnosed IBS patients fulfilling the eligibility criteria were treated with Rifaximin for two weeks and the improvement in their symptoms was recorded. The data were analyzed using SPSS software.Result: A total of 33 participants were included, with a majority being female 22(66.70%). The mean age was 36.58±7.19 years, and the majority 31(93.90%) were nonvegetarian. Abdominal pain was the most common symptom 28(84.80%), followed by diarrhea and bloating. IBS-D was the most predominant diagnosis 25(75.8%). After treatment initiation, 26(78.80%) reported symptom improvement. Among those with improvement, 11(36.40%) reported a nearly 50% reduction in symptoms and 6(18.2%) experienced complete relief.Conclusion: Treatment with Rifaximin resulted in a notable decrease in irritable bowel syndrome symptoms across various subclasses among Nepalese patients.